Preparation method of environment-friendly combined polyether for polyurethane foam material
By using corn starch to prepare starch-based oligopolyethers and mix them with polyether polyols to form an environmentally friendly combined polyether, the problem of high cost of polyol starting agents in the existing polyether type polyurethane foaming material is solved, and the dual goals of high environmental protection and economicality are achieved.
Patent Information
- Application Number
- CN202411730055.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-02-25
AI Technical Summary
The existing polyether polyurethane foaming materials have high cost and low economic value, making it difficult to achieve the dual goals of environmental protection and economicality.
Common and cheap corn starch as the main ingredient, starch-based oligomers are prepared through steps such as drying, pretreatment, esterification and grafting reaction, and mixed with polyether polyols to form an environmentally friendly combined polyether.
The use of starch-derived polyether as raw material is achieved to improve the environmental protection and mechanical properties of polyurethane foaming materials, while reducing production costs.
Smart Images

Figure CN119505148A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of high molecular polyurethane foaming materials, and mainly relates to a method for preparing an environmentally friendly combined polyether for polyurethane foaming materials. Background Art
[0002] Polyurethane foam material is a porous polyurethane material composed of a large number of micropores and polyurethane resin pore wall meridians. It is widely used in the fields of building energy conservation, transportation insulation, cushioning packaging, furniture, medicine, flame retardancy, sound insulation, automobile industry, sporting goods and electronic appliances.
[0003] The main components of polyurethane foam materials are polyols and isocyanates. The production method of polyurethane foam materials is to first react polyols with isocyanates to form prepolymers, and then add foaming agents, catalysts, etc. to carry out foaming reactions. This method can accurately control the reaction process and produce products with stable performance. It is often used to produce high-quality polyurethane foam materials, such as products used in aerospace, high-end automotive parts and other fields.
[0004] Polyurethane foam materials can be classified into polyester type, polyether type and castor oil type polyurethane foam plastics according to the type of polyols. The present application is directed to polyether type polyurethane foam materials. The sources of polyols for polyether type polyurethane foam materials are currently divided into three categories: one is synthesized with low molecular weight polyols as initiators, the second is synthesized with polyamines as initiators, and the third is synthesized with active hydrogen-containing compounds as initiators.
[0005] At present, there are also studies on using green materials such as vegetable oil, starch and other derived polyethers as raw materials to improve the environmental friendliness of polyurethane foam materials.
[0006] For example, the invention patent with patent number 202111103081.4 discloses a polyurethane composition, which includes a combined polyether, a physical foaming agent and an isocyanate. The combined polyether includes a polyol component, based on the mass of the polyol component, the polyol component contains ≥15wt% of a polyether polyol with sucrose as the initiator; the physical foaming agent contains butane, and the molar percentage of butane in the physical foaming agent is greater than 5%; butane is premixed with the combined polyether or isocyanate under the conditions of ≤23°C and an absolute pressure of ≥2.0bar. The present application also proposes a combined polyether for the above-mentioned polyurethane composition, as well as a polyurethane rigid foam and a method for preparing the polyurethane rigid foam.
[0007] The above technical solution is that the polyol component contains ≥15wt% of polyether polyol using sucrose as the initiator. However, the production cost of using sucrose as the initiator of polyether polyol is high and the economic value is low. Summary of the invention
[0008] In view of the above problems, the present invention provides a method for preparing an environmentally friendly combination polyether for polyurethane foaming materials, which uses common and cheap corn starch as the main component to prepare starch-based oligoethers, and mixes the starch-based oligoethers with polyether polyols to form environmentally friendly combination polyethers for polyurethane foaming materials. This achieves the purpose of using starch-derived polyethers as raw materials to improve the environmental friendliness of polyurethane foaming materials, and has low production costs.
[0009] The technical solution adopted by the preparation method of an environmentally friendly composite polyether for polyurethane foam material provided in the present application is as follows: A method for preparing an environmentally friendly composite polyether for a polyurethane foam material, wherein the environmentally friendly composite polyether comprises 10 to 18 parts by weight of starch-based oligoether and the rest are polyether polyols, totaling 100 parts. The method for preparing the environmentally friendly composite polyether comprises the following steps: Step S1, drying treatment, placing the corn starch in a dryer and drying it to a moisture content of less than 5%; Step S2, pretreatment, placing the dried corn starch in a reaction kettle, adding deionized water, introducing nitrogen for replacement for 15-20 minutes, starting a stirring device, stirring at 200-300 r / min for 15-25 minutes; Step S3, adding a catalyst, adding potassium hydroxide catalyst to the reaction kettle, and continuously stirring for 10-15 minutes; Step S4, adding the initiator polyol, dropping polyethylene glycol 400 into the reaction kettle, stirring simultaneously, and continuing stirring for 20-30 minutes after the polyethylene glycol is added; Step S5, esterification reaction, add ethylene oxide and dimethylaniline into the reaction kettle at a rate of 30-50 g / min, keep warm at 120-140° C. for 3-5 hours; Step S6, grafting reaction, cooling, decompressing and removing water, adding propylene carbonate, trimethylene carbonate and o-hydroxybenzoic acid at 65-80° C., stirring for 7-10 hours until no gas is released, heating to 145-160° C., stirring and reacting for 24-30 hours; Step S7, adjusting the viscosity, cooling to room temperature, adding 4-aminophenoxydodecane-1-thiol and a cleavage-type initiator, stirring and reacting under ultraviolet light for 20 to 25 minutes, and post-treating to obtain a starch-based oligoether with a viscosity of 300 to 500 mPa·s, wherein when irradiated with ultraviolet light, the reaction mixture flows outward from the center of the reactor, and is extruded and matched by the annular ultraviolet light belt and the arc-shaped ultraviolet light belt to form a flowing sheet-like irradiation; Step S8: mixing: mixing the prepared starch-based oligoether with the polyether polyol to obtain an environmentally friendly composite polyether.
[0010] Starch-based oligoethers, as biomass-derived oligoethers, partially replace traditional polyether polyols. By optimizing the preparation method of starch-based oligoethers, low polymerization shrinkage is guaranteed, and the polyurethane foam material not only has a good pore distribution, but also has enhanced mechanical properties. Specifically, the hydroxyl and amino groups in the structure of starch-based oligoethers can react and cross-link, so that it has higher molecular energy and intermolecular forces, thereby improving the mechanical properties of polyurethane foam materials, such as tensile strength, compressive strength, etc., making the material more durable. At the same time, in the preparation process of starch-based oligoethers, grafted components such as propylene carbonate and trimethylene carbonate increase the structural space gap, thereby improving the stability of the foaming process, forming uniform pores inside the polyurethane foam material, avoiding internal defects or foam shrinkage, and other problems, thereby improving the overall quality and performance of the material.
[0011] In addition, by grafting 4-aminophenoxydodecane-1-thiol, the viscosity of the starch-based oligoether is reduced, so that the dispersibility of the starch-based oligoether in the polyether combination is better, segregation is suppressed, and the comprehensive performance of the polyurethane foam material is improved.
[0012] In addition, when grafting 4-aminophenoxydodecane-1-thiol, ultraviolet light irradiation is also used to greatly increase the grafting rate. The present invention also adjusts the structure of the reactor, and improves the traditional fixed ultraviolet light irradiation to a flowing thin sheet irradiation, so that the reaction mixture forms a fluid sheet and is irradiated with ultraviolet light, further improving the grafting rate and reaction speed of the material.
[0013] Furthermore, the replacement of traditional polyether polyols with starch-based oligoethers makes polyurethane foam materials more biodegradable and reduces the pollution of the materials to the environment.
[0014] As an improvement, the polyether polyol includes polyether polyol A and polyether polyol B; Polyether polyol A uses glycerol, trimethylolpropane or triethanolamine as an initiator, has a primary hydroxyl content of ≥75%, and a number average molecular weight of 8000-10000; The polyether polyol B uses ethylene glycol, propylene glycol, diethylene glycol or dipropylene glycol as an initiator, has a primary hydroxyl content of ≥80%, and a number average molecular weight of 2000-5000.
[0015] As an improvement, the corn starch is porous corn starch, and the preparation method of the porous corn starch comprises the following steps: Step T1, proportioning: corn starch is added into an appropriate amount of deionized water to prepare a starch suspension with a mass fraction of 10%-30%, the suspension is placed in a constant temperature water bath, stirred evenly at a temperature of 30-50° C., and the stirring speed is set to 300-500 r / min; Step T2, enzymatic hydrolysis reaction, adjusting the pH value of the starch suspension to 5.5-7.0, adding 50 U / g of amylase to the starch suspension, and performing enzymatic hydrolysis reaction at 65° C. for 2-6 hours; Step T3, secondary enzymolysis, adjusting the pH value of the starch suspension to 4.0-4.5, adding 60 U / g of saccharifying enzyme to the starch suspension, and performing enzymolysis reaction at 50-60° C. for 2-4 hours; Step T4, starch recovery: after the enzymatic hydrolysis reaction is completed, the reaction solution is placed in a boiling water bath and heated for 10-15 minutes, the reaction solution is centrifuged at a speed of 4000-6000 r / min for 10-15 minutes, and the precipitated starch is collected; Step T5, washing and drying, washing the starch precipitate with 80% by volume ethanol for 3-5 times, placing the washed starch in a vacuum drying oven, and drying it at a temperature of 40-60° C. for 6-12 hours to obtain porous corn starch.
[0016] The present invention adopts porous corn starch as the main raw material of starch-based oligoether, and in the process of corn starch porosification, two enzymatic hydrolysis methods are adopted to form porous corn starch with high porosity consistency and uniform pore distribution, and the porous structure of porous corn starch helps to improve the pore structure of polyurethane foam material. In the foaming process, it can make the pores more uniform and better connected, thereby improving the sound absorption, heat insulation and other properties of the material. In terms of mechanical properties, porous corn starch-based oligoether can give the material better flexibility and elasticity.
[0017] As an improvement, the raw materials of the starch-based oligoether include the following components; By weight, 50 parts of corn starch, 30 parts of deionized water, 0.5 parts of potassium hydroxide catalyst, 30 parts of polyethylene glycol 400, 80 parts of ethylene oxide, 0.5 parts of dimethylaniline, 25 parts of propylene carbonate, 35 parts of trimethylene carbonate, 0.5 parts of o-hydroxybenzoic acid, 15 parts of 4-aminophenoxydodecane-1-thiol, and 0.5 parts of cleavage initiator.
[0018] As an improvement, the extrusion fit between the annular ultraviolet light strip and the arc-shaped ultraviolet light strip is driven by a rotating stirring paddle in the reaction kettle.
[0019] As an improvement, an irradiation channel with a distance of 20-30 cm is formed between the annular ultraviolet light strip and the inner wall of the reaction kettle.
[0020] As an improvement, four groups of arc-shaped ultraviolet light strips are arranged in an equidistant array along the centerline circumference of the reactor, and the arc-shaped ultraviolet light strips are moved and extruded toward or away from the annular ultraviolet light strips, and elastic connecting strips are arranged between adjacent arc-shaped ultraviolet light strips.
[0021] As an improvement, a 30-60 cm ultraviolet light initial irradiation zone is formed between the arc-shaped ultraviolet light strip and the annular ultraviolet light strip.
[0022] As an improvement, a plurality of one-way valves are evenly distributed on the arc-shaped ultraviolet light strip; When the arc-shaped ultraviolet light belt moves toward the annular ultraviolet light belt, the one-way valve is closed, and when the arc-shaped ultraviolet light belt moves away from the annular ultraviolet light belt, the one-way valve is opened.
[0023] As an improvement, a cylindrical guide rod is extended inward on the inner wall of the reactor, the upper and lower parts of the arc-shaped ultraviolet light strip are slidably arranged along the axial direction of the guide rod, and the inside of the guide rod is hollow, and the positive and negative connecting wires of the arc-shaped ultraviolet light strip and the annular ultraviolet light strip are passed through the guide rod and pass through the reactor to be connected to an external power supply.
[0024] Beneficial effects of the present invention: (1) The present invention uses starch-based oligoether as biomass-derived oligoether to partially replace traditional polyether polyols. By optimizing the preparation method of starch-based oligoether, a low polymerization shrinkage rate is ensured, and the polyurethane foam material not only has a good pore distribution, but also has enhanced mechanical properties. The hydroxyl group and amino group in the structure of starch-based oligoether can react and cross-link, so that it has higher molecular energy and intermolecular force, thereby improving the mechanical properties of the polyurethane foam material, such as tensile strength, compressive strength, etc., making the material more durable. At the same time, in the preparation process of starch-based oligoether, the grafted components such as propylene carbonate and trimethylene carbonate increase the structural space gap, thereby improving the stability of the foaming process, so that uniform pores are formed inside the polyurethane foam material, avoiding problems such as internal defects or foam shrinkage, and thus improving the overall quality and performance of the material; (2) The present invention utilizes the grafting of 4-aminophenoxydodecane-1-thiol to reduce the viscosity of starch-based oligoethers, thereby making the dispersibility of starch-based oligoethers in the polyether combination better and inhibiting segregation, thereby improving the comprehensive performance of the polyurethane foam material. In addition, when grafting 4-aminophenoxydodecane-1-thiol, the grafting rate is greatly increased by ultraviolet light irradiation. The present invention also adjusts the structure of the reactor, and improves the traditional fixed ultraviolet light irradiation to a flowing sheet-like irradiation, so that the reaction mixture forms a flowable sheet and is irradiated with ultraviolet light, further improving the grafting rate and reaction speed of the material; (3) The present invention uses porous corn starch as the main raw material of starch-based oligoethers, and in the process of making corn starch porous, two enzymatic hydrolysis methods are used to form porous corn starch with high porosity consistency and uniform pore distribution. The porous structure of porous corn starch helps to improve the pore structure of polyurethane foaming materials. During the foaming process, it can make the pores more uniform and better connected, thereby improving the sound absorption, heat insulation and other properties of the material. In terms of mechanical properties, porous corn starch-based oligoethers can give the material better flexibility and elasticity.
[0025] In summary, the environmentally friendly combined polyether of the present invention has lower production cost and higher economic value. At the same time, the produced polyurethane foam material has stronger mechanical properties, uniform pore distribution, excellent sound absorption and heat insulation properties, good flexibility and elasticity, and is particularly suitable for the technical field of preparation of polyurethane foam polymer materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is a schematic diagram of the process for preparing the environmentally friendly composite polyether of the present invention; Figure 2 The figure is a schematic diagram of the preparation method of porous corn starch of the present invention; Figure 3 This is a schematic diagram of the front view structure of the reactor of the present invention; Figure 4 It is a schematic diagram of the three-dimensional structure of the reaction kettle of the present invention; Figure 5 It is a schematic diagram of the cross-sectional structure of the reaction kettle of the present invention; Figure 6 It is a schematic diagram of the three-dimensional structure of the lower kettle body of the present invention; Figure 7 for Figure 6 The enlarged structural diagram at A in the middle; Figure 8 This is a schematic diagram of the three-dimensional structure of the arc-shaped ultraviolet light strip of the present invention; Fig. 9 It is a schematic diagram of the three-dimensional structure of the linear ball bearing of the present invention; Fig.10 This is a schematic diagram of the one-way valve of the present invention in an open state; Fig.11 This is a schematic diagram of the one-way valve of the present invention in a closed state; Fig.12 This is a schematic diagram of the connection structure of the arc-shaped ultraviolet light strip of the present invention; Fig.13 This is a schematic diagram of the transverse cross-sectional structure of the annular ultraviolet light strip of the present invention; Fig.14 for Fig.13 A magnified schematic diagram of the structure at B in the middle; Fig.15This is a front view structural schematic diagram of the annular ultraviolet light belt of the present invention; Fig.16 This is a schematic diagram of the structure of the arc-shaped ultraviolet light strip driven by the stirring paddle of the present invention.
[0027] 1 , agitator 3, driver 31 , stirring paddle 32 , disc 321 , guide groove 322 , pull-back portion 3221 , push-pull portion 3222 , ultraviolet irradiation device 4 , annular ultraviolet light strip 41 , transparent shell 411 , connecting hole 4111 , ultraviolet light strip 412 , arc-shaped ultraviolet light strip 42 , linear ball bearing 421 , corrugated rubber sleeve 422 , roller 423 , one-way valve 424 , valve body 4241 , flow hole 4242 , discharge hole 4243 , valve ball 4244 , rubber belt 43 . DETAILED DESCRIPTION
[0028] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0029] In the description of the present invention, it should be understood that the terms "center", "longitudinal", "lateral", "length", "width", "thickness", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", "clockwise", "counterclockwise" and the like indicate orientations or positional relationships based on the orientations or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present invention and simplifying the description, and do not indicate or imply that the referred device or element must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as a limitation on the present invention.
[0030] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. In the description of the present invention, the meaning of "plurality" is two or more, unless otherwise clearly and specifically defined.
[0031] Embodiment 1: like Figure 1As shown, a method for preparing an environmentally friendly combined polyether for polyurethane foaming material: The environmentally friendly composite polyether includes 10 to 18 parts of starch-based oligoether and the rest of the polyether polyols, totaling 100 parts by weight. The preparation method of the environmentally friendly composite polyether includes the following steps: Step S1, drying treatment, placing the corn starch in a dryer and drying it to a moisture content of less than 5%; Step S2, pretreatment, placing the dried corn starch in a reaction kettle, adding deionized water, introducing nitrogen for replacement for 15-20 minutes, so that the kettle is in a nitrogen protective atmosphere to prevent adverse conditions such as starch oxidation, and starting a stirring device, stirring at 200-300 r / min for 15-25 minutes to make the starch in a uniformly dispersed state; Step S3, adding a catalyst, adding potassium hydroxide catalyst to the reaction kettle, and continuing stirring for 10-15 minutes. The potassium hydroxide catalyst catalyzes the etherification reaction; Step S4, adding the initiator polyol, dropping polyethylene glycol 400 into the reaction kettle, stirring simultaneously, and after the polyethylene glycol is added, stirring is continued for 20-30 minutes to allow the starch, catalyst and initiator polyol to be fully mixed to form a uniform mixture; Step S5, esterification reaction, add ethylene oxide and dimethylaniline into the reactor at a rate of 30-50 g / min to avoid excessive reaction. As ethylene oxide is introduced, the reaction will gradually release heat. The reaction temperature is controlled by the jacket circulating cooling water system of the reactor to maintain the temperature at 120-140° C. This temperature range is conducive to the efficient and stable etherification reaction. Keep the temperature for 3-5 hours to initially obtain starch-based oligoethers; Step S6, grafting reaction, cooling, decompressing and removing water, adding propylene carbonate, trimethylene carbonate, and o-hydroxybenzoic acid at 65-80° C., stirring for 7-10 hours until no gas is released, heating to 145-160° C., stirring and reacting for 24-30 hours, using the grafting of propylene carbonate and trimethylene carbonate to increase the structural space gap, thereby improving the stability of the foaming process, forming uniform pores inside the polyurethane foam material, and avoiding problems such as internal defects or foam shrinkage; Step S7, adjusting the viscosity, cooling to room temperature, adding 4-aminophenoxydodecane-1-thiol and a cleavage initiator, stirring and reacting under ultraviolet light for 20 to 25 minutes, and post-treating to obtain the final starch-based oligoether; During ultraviolet irradiation, the reaction mixture flows outward from the center of the reactor, and is squeezed and matched by the annular ultraviolet light strip and the arc ultraviolet light strip to form a flowing thin-sheet irradiation. The flowing thin-sheet irradiation technology can greatly increase the grafting rate of 4-aminophenoxydodecane-1-thiol and reduce the viscosity of starch-based oligoethers (when starch-based oligoethers are used in polyurethane foaming materials, the viscosity is generally controlled at 100-1000mPa・s (25℃) which is more appropriate. This viscosity range can ensure that it has good fluidity in the foaming system and is easy to operate during mixing and infusion. Lower viscosity (such as less than 100m The viscosity of the starch-based oligoether is too high (e.g., greater than 1000 mPa·s) which may cause the starch-based oligoether to diffuse too quickly during the foaming process, affecting its distribution on the cell wall and hindering its performance; while too high a viscosity (e.g., greater than 1000 mPa·s) will make mixing difficult, increase stirring resistance, and may result in incomplete filling when pouring into the mold. The present invention can achieve an optimal viscosity of 300-500 mPa·s) for the starch-based oligoether within 20 to 25 minutes through flow-type sheet-like irradiation, thereby improving the dispersibility of the starch-based oligoether in the polyether combination, inhibiting segregation, and thus improving the comprehensive performance of the polyurethane foam material; Step S8: mixing: mixing the prepared starch-based oligoether with the polyether polyol to obtain an environmentally friendly composite polyether.
[0032] Specifically, the raw materials of the starch-based oligoether include the following components: By weight, 50 parts of corn starch, 30 parts of deionized water, 0.5 parts of potassium hydroxide catalyst, 30 parts of polyethylene glycol 400, 80 parts of ethylene oxide, 0.5 parts of dimethylaniline, 25 parts of propylene carbonate, 35 parts of trimethylene carbonate, 0.5 parts of o-hydroxybenzoic acid, 15 parts of 4-aminophenoxydodecane-1-thiol, and 0.5 parts of cleavage initiator.
[0033] Wherein, the polyether polyol comprises polyether polyol A and polyether polyol B; Polyether polyol A uses glycerol, trimethylolpropane or triethanolamine as an initiator, has a primary hydroxyl content of ≥75%, and a number average molecular weight of 8000-10000; The polyether polyol B uses ethylene glycol, propylene glycol, diethylene glycol or dipropylene glycol as an initiator, has a primary hydroxyl content of ≥80%, and a number average molecular weight of 2000-5000.
[0034] It should be noted that when starch-based oligoethers partially replace traditional polyether polyols, such as polyoxypropylene diol, polyoxypropylene triol, high-activity polyether polyols, polytetrahydrofuran diol, etc., the number average molecular weight of the above-mentioned polyether polyols is lower than 6000. Therefore, when preparing polyurethane foam materials, the environmentally friendly composite polyether also needs to contain a certain number average molecular weight of 8000-10000 polyether polyol A, and some polyether polyols B with a number average molecular weight of 2000-5000 that cannot be replaced.
[0035] Specifically, the content of polyether polyol A is 30-50 parts by weight, and the content of polyether polyol B is 30-40 parts by weight.
[0036] like Figure 2 As shown, further, the corn starch is porous corn starch, and the preparation method of porous corn starch comprises the following steps; Step T1, proportioning: corn starch is added into an appropriate amount of deionized water to prepare a starch suspension with a mass fraction of 10%-30%, the suspension is placed in a constant temperature water bath, stirred evenly at a temperature of 30-50° C., and the stirring speed is set to 300-500 r / min; Step T2, enzymatic hydrolysis reaction, adjusting the pH value of the starch suspension to 5.5-7.0, adding 50 U / g of amylase to the starch suspension, and performing enzymatic hydrolysis reaction at 65° C. for 2-6 hours; Step T3, secondary enzymolysis, adjusting the pH value of the starch suspension to 4.0-4.5, adding 60 U / g of saccharifying enzyme to the starch suspension, and performing enzymolysis reaction at 50-60° C. for 2-4 hours; Step T4, starch recovery: after the enzymatic hydrolysis reaction is completed, the reaction solution is placed in a boiling water bath and heated for 10-15 minutes, the reaction solution is centrifuged at a speed of 4000-6000 r / min for 10-15 minutes, and the precipitated starch is collected; Step T5, washing and drying, washing the starch precipitate with 80% by volume ethanol for 3-5 times, placing the washed starch in a vacuum drying oven, and drying it at a temperature of 40-60° C. for 6-12 hours to obtain porous corn starch.
[0037] It should be noted that porous corn starch has the following advantages over ordinary corn starch when used to prepare starch-based oligoethers: Higher reactivity: Porous corn starch has a large specific surface area and rich pore structure, which greatly increases its contact area with reaction reagents such as propylene oxide, thereby improving the activity and efficiency of the reaction, which is conducive to the full progress of the etherification reaction and can achieve a high degree of substitution in a relatively short time, thereby improving the performance of starch-based oligoethers; Better adsorption performance: Its pores can absorb more reaction raw materials and catalysts, making the distribution of various substances in the reaction system more uniform, promoting the reaction, and also helping to improve the stability and performance uniformity of the product. In addition, good adsorption performance can also enable starch-based oligoethers to better adsorb other substances during the application process, such as when used as an adsorbent or carrier, it can more effectively adsorb and fix the target substance; Better mechanical properties: The porous structure can increase the toughness and elasticity of starch-based oligoethers, so that they can better absorb and disperse energy when subjected to external forces, reduce stress concentration, and thus improve the mechanical properties of the material such as impact resistance and tensile strength. In some application fields that require good mechanical properties, such as the preparation of sound-absorbing sponge strips, starch-based oligoethers prepared using porous corn starch can better meet the use requirements of the product; Good foaming performance: In the process of preparing starch-based oligoethers, the pores of porous corn starch can be used as nucleation points for foaming, which is conducive to the formation of uniform and fine bubbles, thereby improving the foaming efficiency and foam stability, and making the prepared materials have better sound absorption, heat insulation, cushioning and other properties. For example, in the preparation of automotive sound-absorbing sponge strips, the use of starch-based oligoethers prepared based on porous corn starch can increase the structural space gap, improve the foaming stability, produce uniform pores inside the sponge, and enhance the sound insulation; Adjustable performance: By changing the preparation process and parameters of porous corn starch, its pore size, pore volume, specific surface area and other structural characteristics can be adjusted, thereby achieving the adjustment of the performance of starch-based oligoethers to meet the diverse requirements of different application fields and products for material performance.
[0038] The use of amylase and saccharifying enzyme to form porous corn starch has the following advantages over the conventional enzymatic method: Amylases (such as α-amylase) can randomly act on the α-1,4-glycosidic bonds inside starch molecules, causing the starch to hydrolyze rapidly to produce dextrins and oligosaccharides. Saccharifying enzymes (such as glucoamylase) can hydrolyze the α-1,4-glycosidic bonds from the non-reducing ends of starch molecules in sequence, further hydrolyzing dextrins and the like into glucose. The synergistic effect of these two enzymes can enable faster and more comprehensive hydrolysis reactions inside and on the surface of starch granules. Compared with the single enzymatic hydrolysis method, the two-step enzymatic hydrolysis method can produce more hydrolysis sites in a shorter time, causing the structure inside the starch granules to be destroyed more quickly, thereby accelerating the formation of a porous structure.
[0039] In the same reaction time, the porosity of porous corn starch obtained by two-step enzymatic hydrolysis may be 20%-30% higher than that of ordinary enzymatic hydrolysis. For example, the porosity of ordinary enzymatic hydrolysis reaches 30% after 4 hours, while the porosity of two-step enzymatic hydrolysis can reach about 40% after 3 hours.
[0040] In addition, amylase mainly creates preliminary holes inside starch granules, breaking the starch molecular chains and producing relatively uneven holes and cracks. Saccharifying enzymes further act on these preliminary hydrolysis products, finely hydrolyzing the starch molecules at the edges and inside the holes, making the pore walls smoother and adjusting the size and shape of the holes. This synergistic effect can produce pore structures of various sizes, from micropores to mesopores, while ordinary enzymatic hydrolysis may only form a relatively single type of pores.
[0041] Scanning electron microscopy observations revealed that the porous corn starch prepared by the two-step enzymatic hydrolysis method has a variety of pores with diameters ranging from a few nanometers to tens of micrometers, while the pores produced by the ordinary enzymatic hydrolysis method may mainly have pores with diameters concentrated in a smaller range, such as pores of 1-10 microns. The two-step enzymatic hydrolysis method may simultaneously produce micropores smaller than 1 micron and macropores larger than 10 microns.
[0042] Moreover, since the porous structure formed by the two-step enzymatic hydrolysis method is richer and more complete, the prepared porous corn starch performs better in terms of adsorption performance and specific surface area. The rich pore structure enables it to adsorb more types and larger volumes of substances, and the increase in specific surface area is also conducive to physical or chemical interactions with other substances. In terms of application, for example, when used as an adsorbent or carrier in the fields of food and medicine, its adsorption capacity and stability may be better.
[0043] Embodiment 2: In addition, the present invention also provides a reaction kettle specially used for preparing starch-based oligoethers.
[0044] like Figures 3 to 16 As shown, the reactor comprises a reactor body 1, a nitrogen input device 2, a stirring device 3 and an ultraviolet light irradiation device 4; The kettle body 1 is composed of a kettle cover 11 and a lower kettle body 12. The kettle cover 11 is provided with a feed hole 111. The lower kettle body 12 is provided with a reaction chamber. The bottom of the lower kettle body 12 is provided with a discharge port 121. A valve (not shown in the figure) is provided at the discharge port 121. The outer cover of the lower kettle body 12 is provided with a heat-insulating jacket 120 for adjusting the temperature. The nitrogen input device 2 is arranged on the top of the kettle cover 11, and the nitrogen input device 2 includes a nitrogen input pipe 21, a pneumatic ball valve 22 and a two-piece internal thread ball valve 23. The nitrogen input pipe 21 consists of a main pipe 211 and a branch pipe 212. The main pipe 211 is arranged vertically, and a pneumatic ball valve 22 for controlling the on-off of the main pipe 211 is installed on it. The branch pipe 212 is connected to the two ends of the pneumatic ball valve 22 on the main pipe 211. The branch pipe 212 is used to adjust the air pressure in the main pipe 211, and a two-piece internal thread ball valve 23 for controlling its on-off is arranged on the branch pipe 212; The stirring device 3 penetrates the kettle cover 11 and is arranged in the lower kettle body 12. The stirring device 3 includes a driver 31 and a stirring paddle 32. The driver 31 is arranged on the top of the kettle cover 11. The driver 31 is preferably a servo motor. The stirring paddle 32 is rotatably arranged in the lower kettle body 12. The top of the stirring paddle 32 is transmission-connected to the driver 31. The driver 31 drives the stirring paddle 32 to rotate and stir in the lower kettle body 12.
[0045] The ultraviolet light irradiation device 4 includes an annular ultraviolet light strip 41 and an arc-shaped ultraviolet light strip 42, wherein the annular ultraviolet light strip 41 is arranged in a circular ring shape, the annular ultraviolet light strip 41 and the lower kettle body 12 are arranged coaxially, and an irradiation flow channel with a distance of 20-30 cm is formed between the annular ultraviolet light strip 41 and the inner wall of the lower kettle body 12, and the reaction mixture is diluted to 20-30 cm in the irradiation flow channel to contact the ultraviolet light emitted by the annular ultraviolet light strip 41; The arc-shaped ultraviolet light strip 42 is arranged in an arc shape, and four groups of the arc-shaped ultraviolet light strips 42 are arranged in an equidistant array along the center line circumference of the lower kettle body 12, and the arc-shaped ultraviolet light strips 42 are moved and extruded toward or away from the annular ultraviolet light strip 41, and a 30-60 cm ultraviolet light initial irradiation area is formed between the arc-shaped ultraviolet light strip 42 and the annular ultraviolet light strip 41.
[0046] like Figure 13-14 As shown, specifically, the annular ultraviolet light strip 41 and the arc-shaped ultraviolet light strip 42 both include a transparent shell 411 and a lamp post 412. The transparent shell 411 is made of quartz glass or high borosilicate glass with a thickness of about 10 cm, and the power of the lamp post 412 is 30-50 watts. A lamp post 412 with too high a power and a transparent shell that is too thin will result in a very high intensity of ultraviolet light on the surface of the reactants when the reactants are very close, which may excessively damage the chemical bonds of the reactants (such as the starch molecular structure, the reagent molecules involved in the reaction, etc.), causing unnecessary abnormal changes such as cracking and polymerization, deviating from the expected reaction process and product structure requirements.
[0047] like Figure 6 As shown, further, a cylindrical guide column 122 is extended inwardly on the inner wall of the lower kettle body 12, and the upper and lower parts of the annular ultraviolet light strip 41 are fixedly mounted on the guide column 122, and the guide column 122 located at the lower part of the lower kettle body 12 is hollow, and a strip-shaped notch 123 is opened on the upper part of the guide column 122, and the positive and negative connecting wires of the annular ultraviolet light strip 41 pass through the notch 123 and pass through the lower kettle body; like Figure 8-Figure 9As shown, the upper and lower parts of the arc-shaped ultraviolet light strip 42 are both slidably arranged along the axial direction of the guide rod 122, and linear ball bearings 421 are installed on the upper and lower parts of the arc-shaped ultraviolet light strip 42. The linear ball bearings 421 are rollingly sleeved with the guide column 122, so that the arc-shaped ultraviolet light strip 42 can slide smoothly on the guide rod 122, and when the arc-shaped ultraviolet light strip 42 slides, the positive and negative connecting lines on the arc-shaped ultraviolet light strip 42 are dragged through the notch 123, and corrugated rubber sleeves 422 are connected to both sides of the outside of the linear ball bearing 421, and the corrugated rubber sleeves 422 can be folded and compressed, so that the linear ball bearing 421 is completely isolated and does not contact with the external mixed reactants, and the notch 123 is also sealed.
[0048] Before ultraviolet light irradiation, the annular ultraviolet light strip 41 and the arc ultraviolet light strip 42 are energized to light up the ultraviolet lamp column 412 inside thereof. After the ultraviolet lamp column 412 is lit, the mixed reactants in the lower kettle body 12 are continuously diluted by extrusion through the ultraviolet initial irradiation area and the irradiation flow channel through the movement of the arc ultraviolet light strip 42, so that the mixed reactants in the two places are completely irradiated by ultraviolet light, thereby achieving the purpose of promoting the grafting rate of 4-aminophenoxydodecane-1-thiol and reducing the viscosity of starch-based oligoethers.
[0049] like Fig.16 As shown, further, the movement of the arc-shaped ultraviolet light strip 42 is driven by the stirring device 3. Specifically, a disc 321 is arranged on the stirring paddle 32, and a curved guide groove 322 is arranged at the lower end of the disc 321. The guide groove 322 is composed of a plurality of groups of inwardly recessed pull-back portions 3221 and a plurality of groups of outwardly protruding push-out portions 3222. Correspondingly, a roller 423 is arranged at the lower end of each group of the arc-shaped ultraviolet light strip 42, and the roller 423 is placed in the guide groove 322. When the disc 321 rotates, the pull-back portion 3221, the push-out portion 3222 and the roller 423 are alternately matched, so that the arc-shaped ultraviolet light strip 42 slides on the guide rod 122. The arc-shaped ultraviolet light strip 42 moves, so that the distance between the arc-shaped ultraviolet light strip 42 and the annular ultraviolet light strip 41 is continuously changed, so that the mixed reactants in the initial irradiation area of the squeezed ultraviolet light are continuously diluted.
[0050] like Fig.12As shown, further, adjacent arc-shaped ultraviolet light strips 42 are connected by flexible and compressible rubber strips 43, so that the arc-shaped ultraviolet light strips 42 form a group of ultraviolet light strips with variable diameters through the rubber strips 43, and the arc-shaped ultraviolet light strips 42 cooperate with the annular ultraviolet light strips 41 to achieve the goal of converting a large range of mixed reactants in the lower kettle body 12 into a small range of rapidly flowing ultraviolet light for irradiation, thereby avoiding the mixed reactants from being irradiated by ultraviolet light for a long time and promoting the grafting rate and grafting rate of 4-aminophenoxydodecane-1-thiol through the irradiation of ultraviolet light.
[0051] like Fig.15 As shown, furthermore, the transparent shell 411 of the annular ultraviolet light strip 41 is evenly provided with connecting holes 4111 connecting the ultraviolet light initial irradiation area with the irradiation flow channel, and the corresponding arc-shaped ultraviolet light strip 42 is evenly provided with a plurality of one-way valves 424; like Figure 8-Figure 11 As shown, the specific structure of the one-way valve 424 includes a cylindrical valve body 4241, a through flow hole 4242 is opened on the valve body 4241, a through discharge hole 4243 is arranged on the side wall of the valve body 4241, the discharge hole 4243 is connected to the flow hole 4242, and a floating valve ball 4244 is arranged in the flow hole 4242, and the valve ball 4244 moves with the flow impact of the mixed reactants.
[0052] When the arc-shaped ultraviolet light strip 42 moves toward the annular ultraviolet light strip 41, the one-way valve 424 is closed (the valve ball 4244 is impacted by the flow of the mixed reactants, so that the valve ball 4244 blocks the flow hole 4242, and the flow hole 4242 cannot connect the inner and outer sides of the arc-shaped ultraviolet light strip 42, thereby achieving the closure of the one-way valve 424), so that the mixed reactants in the ultraviolet initial irradiation area are squeezed into the irradiation channel through the connecting hole 4111, thereby accelerating the flow of the mixed reactants in the ultraviolet initial irradiation area and the irradiation channel, and making the ultraviolet light irradiation more sufficient.
[0053] When the arc-shaped ultraviolet light strip 42 moves away from the annular ultraviolet light strip 41, the one-way valve 424 opens (the valve ball 4244 is impacted by the flow of the mixed reactants, so that the valve ball 4244 rolls to the rear side of the discharge hole 4243, so that the flow hole 4242 connects the inner and outer sides of the arc-shaped ultraviolet light strip 42, and the mixed reactants on the outside of the arc-shaped ultraviolet light strip 42 enter the ultraviolet light initial irradiation area through the flow hole 4242 and the discharge hole 4243, so that the one-way valve 424 is opened), so that the mixed reactants outside the ultraviolet light initial irradiation area are replenished into the ultraviolet light initial irradiation area through the connecting hole one-way valve 424, so as to achieve the purpose of rapid flow.
[0054] In addition, in order to promote the fluidity of the mixed reactants under ultraviolet light irradiation, a circulation pipeline can be set between the discharge port 121 and the lower kettle body 12. Through the circulation pipeline, the mixed reactants at the discharge port 121 are guided to the top of the lower kettle body 12 for repeated circulation.
[0055] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing an environmentally friendly composite polyether for polyurethane foaming material, characterized in that: The environmentally friendly composite polyether includes 10 to 18 parts of starch-based oligoether and the rest of the polyether polyols, totaling 100 parts by weight. The preparation method of the environmentally friendly composite polyether includes the following steps: Step S1, drying treatment, placing the corn starch in a dryer and drying it to a moisture content of less than 5%; Step S2, pretreatment, placing the dried corn starch in a reaction kettle, adding deionized water, introducing nitrogen for replacement for 15-20 minutes, starting a stirring device, stirring at 200-300 r / min for 15-25 minutes; Step S3, adding a catalyst, adding potassium hydroxide catalyst to the reaction kettle, and continuously stirring for 10-15 minutes; Step S4, adding the initiator polyol, dropping polyethylene glycol 400 into the reaction kettle, stirring simultaneously, and continuing stirring for 20-30 minutes after the polyethylene glycol is added; Step S5, esterification reaction, add ethylene oxide and dimethylaniline into the reaction kettle at a rate of 30-50 g / min, keep warm at 120-140° C. for 3-5 hours; Step S6, grafting reaction, cooling, decompressing and removing water, adding propylene carbonate, trimethylene carbonate and o-hydroxybenzoic acid at 65-80° C., stirring for 7-10 hours until no gas is released, heating to 145-160° C., stirring and reacting for 24-30 hours; Step S7, adjusting the viscosity, cooling to room temperature, adding 4-aminophenoxydodecane-1-thiol and a cleavage-type initiator, stirring and reacting under ultraviolet light for 20 to 25 minutes, and post-treating to obtain a starch-based oligoether with a viscosity of 300 to 500 mPa·s, wherein when irradiated with ultraviolet light, the reaction mixture flows outward from the center of the reactor, and is extruded and matched by the annular ultraviolet light belt and the arc-shaped ultraviolet light belt to form a flowing sheet-like irradiation; Step S8: mixing: mixing the prepared starch-based oligoether with the polyether polyol to obtain an environmentally friendly composite polyether.
2. The method for preparing an environmentally friendly composite polyether for polyurethane foam material according to claim 1, characterized in that: The polyether polyol comprises polyether polyol A and polyether polyol B; Polyether polyol A uses glycerol, trimethylolpropane or triethanolamine as an initiator, has a primary hydroxyl content of ≥ 75%, and a number average molecular weight of 8000-10000; Polyether polyol B uses ethylene glycol, propylene glycol, diethylene glycol or dipropylene glycol as an initiator, has a primary hydroxyl content of ≥80%, and a number average molecular weight of 2000-5000.
3. The method for preparing an environmentally friendly composite polyether for polyurethane foam material according to claim 1, characterized in that: The corn starch is porous corn starch, and the preparation method of the porous corn starch comprises the following steps: Step T1, proportioning: corn starch is added into an appropriate amount of deionized water to prepare a starch suspension with a mass fraction of 10%-30%, the suspension is placed in a constant temperature water bath, stirred evenly at a temperature of 30-50°C, and the stirring speed is set to 300-500r / min; Step T2, enzymatic hydrolysis reaction, adjusting the pH value of the starch suspension to 5.5-7.0, adding 50 U / g of amylase to the starch suspension, and performing enzymatic hydrolysis reaction at 65° C. for 2-6 hours; Step T3, secondary enzymolysis, adjusting the pH value of the starch suspension to 4.0-4.5, adding 60U / g of saccharifying enzyme to the starch suspension, and performing enzymolysis reaction at 50-60°C for 2-4 hours; Step T4, starch recovery: after the enzymatic hydrolysis reaction is completed, the reaction solution is placed in a boiling water bath and heated for 10-15 minutes, the reaction solution is centrifuged at a speed of 4000-6000 r / min for 10-15 minutes, and the precipitated starch is collected; Step T5, washing and drying, washing the starch precipitate with 80% by volume ethanol for 3-5 times, placing the washed starch in a vacuum drying oven, and drying at a temperature of 40-60° C. for 6-12 hours to obtain porous corn starch.
4. The method for preparing an environmentally friendly composite polyether for polyurethane foam material according to claim 1, characterized in that: The raw materials of the starch-based oligoether include the following components; By weight, 50 parts of corn starch, 30 parts of deionized water, 0.5 parts of potassium hydroxide catalyst, 30 parts of polyethylene glycol 400, 80 parts of ethylene oxide, 0.5 parts of dimethylaniline, 25 parts of propylene carbonate, 35 parts of trimethylene carbonate, 0.5 parts of o-hydroxybenzoic acid, 15 parts of 4-aminophenoxydodecane-1-thiol, and 0.5 parts of cleavage initiator.
5. The method for preparing an environmentally friendly composite polyether for polyurethane foam material according to claim 1, characterized in that: The extrusion matching of the annular ultraviolet light strip and the arc-shaped ultraviolet light strip is driven by a rotating stirring paddle in the reaction kettle.
6. The method for preparing an environmentally friendly composite polyether for polyurethane foam material according to claim 1, characterized in that: An irradiation channel with a distance of 20-30 cm is formed between the annular ultraviolet light belt and the inner wall of the reaction kettle.
7. The method for preparing an environmentally friendly composite polyether for polyurethane foam material according to claim 1, characterized in that: Four groups of arc-shaped ultraviolet light strips are arranged in an equidistant array along the central line circumference of the reactor, and the arc-shaped ultraviolet light strips are moved and extruded toward or away from the annular ultraviolet light strip, and elastic connecting strips are arranged between adjacent arc-shaped ultraviolet light strips.
8. The method for preparing an environmentally friendly composite polyether for polyurethane foaming material according to claim 1, characterized in that: An initial ultraviolet light irradiation area of 30-60 cm is formed between the arc-shaped ultraviolet light strip and the annular ultraviolet light strip.
9. The method for preparing an environmentally friendly composite polyether for polyurethane foam material according to claim 1, characterized in that: A plurality of one-way valves are evenly distributed on the arc-shaped ultraviolet light strip; When the arc-shaped ultraviolet light belt moves toward the annular ultraviolet light belt, the one-way valve is closed, and when the arc-shaped ultraviolet light belt moves away from the annular ultraviolet light belt, the one-way valve is opened.
10. The method for preparing an environmentally friendly composite polyether for polyurethane foam material according to claim 1, characterized in that: A cylindrical guide rod is extended inwardly on the inner wall of the reactor, and the upper and lower parts of the arc-shaped ultraviolet light strip are slidably arranged along the axial direction of the guide rod, and the inside of the guide rod is hollow. The positive and negative connecting wires of the arc-shaped ultraviolet light strip and the annular ultraviolet light strip are passed through the guide rod and pass through the reactor to be connected to an external power supply.
Citation Information
Patent Citations
Polyurethane compositions, polyether blends, rigid polyurethane foams and their preparation methods
CN113929852B